Missing pieces, new patterns: the impact of association football international call-ups on team offensive and defensive performance indicators - Campos, J.; Gonçalves, B.; Travassos, B.; Mateus, N.; Ballester Lengua, R.; Figueira, B.; Olthof, S.; Coutinho, D. (Frontiers in Psychology, 2026)
Introduction: To examine how mid-season international call-ups (AFCON and AFC Asian Cup) affect club performance across offensive, defensive, and playing-style key performance indicators (KPIs).